Light incoupling and optical optimisation of organic solar cells - Meiss, J; Schueppel, R; Timmreck, R; Furno, M; Uhrich, C; Sonntag, S; Gnehr, W; Pfeiffer, M; Leo, K; Riede, M (2010)
Small-molecule organic solar cells (OSC) are developing towards maturity. For top-illuminated devices, device optimisation and tandem OSCs, interference effects, light trapping and thin film optics are decisive for optimal utilisation of the absorbing layers. We present transparent capping layers that allow for reduced external reflection and improved light incoupling when used in combination with thin metal top contacts. Similarly, transparent spacer layers are used in tandem devices to place the subcells at specific positions in the stack such as to utilise optical field maxima. The results are solar cells with high transparency in the visible region of the light spectrum and as well as world record tandem devices. © Optical Society of America.